The impact of sediment-synoptic processes of сentral Аsia on mountain rivers runoff (Journal of Geography and Environmental Management, 2019)
In this paper we examined the relationship between synoptic processes that determine weather and river runoff. The relationshipbetween rainfall runoff from the rivers. Identifi ed sediment-synoptic processes and their relation to runoff of mountain rivers.